Empathy and prosocial: An interfaith psychology study among Ternate City students - Munadiyah, Siti; Latief, Nurulsani S Abd; Ismail, Abdullah (Universitas Ahmad Dahlan, 2025)
The diversity of religions, cultures, and universities in Ternate City gives rise to social dynamics that are not only complex but also hold great potential to strengthen human and national solidarity, or, conversely, to foster significant disharmony. Therefore, this study aims to explore the interfaith psychological approach, empathy, and prosocial behaviors as efforts to promote harmonious social relations. Specifically, it seeks to identify forms of empathy and prosocial behavior in interfaith interactions among Muslim and non-Muslim students in Ternate City. Using a qualitative phenomenological method, this study explores students' subjective experiences in understanding and expressing empathy, and how these experiences manifest in interfaith prosocial actions. The study involved 15 respondents. Data were collected through observation, in-depth interviews, and focus group discussions (FGDs), and analyzed using the phenomenological approach of Moustakas and Husserl, which includes the stages of epoche, phenomenological reduction, imaginative variation, and synthesis of meaning. The research identified three main themes of empathy: Affective Empathy, arising from spiritual values; Compassionate Empathy, serving as the foundation for emotional support; and Intellectual Empathy, emphasizing rationality in conflict resolution. The study concludes that empathy and prosocial behavior are essential foundations for strengthening interfaith solidarity and contribute significantly to character development in higher education settings.